FAKTOR-FAKTOR DALAM PELAKSANAAN GERAKAN LITERASI SEKOLAH (GLS) DI SMA NEGERI 12 PEKANBARU - Delima Afrilia Manulang; Hambali Hambali; Supentri Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrack: this research was effected by several factors that are considered to greatly affect the implementation of the Literacy Movement Schools which further shortened with GLS good which is an inhibitor of factor or factor endowments in the implementation of the GLS in SMA Negeri 12 Pekanbaru. Formulation of the problem in this research is "what are the factors in the implementation of the GLS in SMA Negeri 12 Pekanbaru?". This research aims to find out what factors in the implementation of the GLS in SMA Negeri 12 Pekanbaru. This research was conducted at SMA Negeri 12 Pekanbaru in August-September 2018. This research is quantitative deskriftif which became the population in this research is 79 Teachers and learners 1185 total amounted to 1261. The sample in this study is taken based on the technique of "Stratified Sample". Where the class is taken i.e. XI and class teacher. Data collection instruments namely observation, documentation, question form and interview. Data Analysis with quantitative descriptive. The calculation of the percentage of overall respondents answer on factor endowments by respondents learners with indicators and infrastructure which stated "Yes" i.e. of 96.03%. And infrastructure by the 8th guru of respondents (eight) sub indicator of 100%, but on understanding indicators educators and education amounted to 95%, and on the power indicator support Government of 68.75%. Then it can be inferred the factors in the implementation of the GLS in SMA Negeri 12 Pekanbaru that a factor supporting most high is an indicator of "facilities and infrastructure", while the teacher the highest barrier to be a factor in the implementation of the GLS in SMA Negeri 12 Pekanbaru is an indicator of "Power support Community".Keywords: Factors, School Literacy Movement